(untitled) (Physical Education, Health and Social Sciences, 2025)
This research investigates the flow and heat transfer characteristics of hybrid nanofluids, which are suspensions of two different nanoparticles in a base fluid. The study focuses on converting the governing partial differential equations (PDEs) of hybrid nanofluid flow into a system of ordinary differential equations (ODEs) using similarity transformations. These ODEs are then solved numerically using MATLAB’s bvp4c solver. The effects of various parameters on the velocity and temperature profiles are analyzed, providing insights into the behavior of hybrid nanofluids under different conditions.